The Impact of Rewards, Job Stress, Job Characteristics, Dispositional Affect toward Job Satisfaction of Ride Hailing Motorbike Drivers in Indonesia - Jonathan Joseph Raharjo; Wilson Febrianto (iBuss Management, 2019)
In the digital economy, the integration of technology in the business is inevitable. Many businesses emerge because of the integration of technology. One of them is the ride-hailing service in Indonesia. Ride-hailing service is perceived as a big contributor in the Indonesian economy, which is more than 10 trillion rupiahs annually. However, there is still a huge problem that caused a massive demonstration, which is conducted by the ride-hailing motorbike driver in Indonesia. Rewards, job stress, job characteristics, dispositional affect are said to be the determinants that can influence job satisfaction. Therefore, this research is to identify the influence of the four-factor on job satisfaction of the ride-hailing motorbike driver in Indonesia.In this research, the researcher use simple random sampling as its sampling method. After that, 85 data from 85 ride-hailing motorbike drivers that have passed the screening question have been gathered. All data have passed the validity test, reliability test, and Classical Assumption. Next, the data is processed with multiple linear regression. The result obtained from this analysis shows that at least one of those four factors influence job satisfaction. However, only job characteristics and dispositional affect influence the job satisfaction of ride-hailing motorbike driver in Indonesia individually. Keywords: Job Satisfaction, Ride Hailing Motorbike Drivers